State imperatives and hopeful futures in outside lobbying campaigns: A case study on sunsetting industries in Finland - Lempinen, Hanna (Elsevier, 2025)
The demands for a just and green transition towards more sustainable use of natural resources—both renewable and nonrenewable, living and non-living—are shaping the prospects of local and traditional livelihoods worldwide. While “green” sustainability transitions are expected to create new livelihoods and economies, others are bound to decline or disappear. This article focuses on Finland and its two traditional rural industries—fur farming and peat extraction—whose phase-out is either ongoing or under debate due to various sustainability concerns. Through an analysis of industry lobbying campaigns, I demonstrate how these industries frame themselves as instrumental in fulfilling core state imperatives, including domestic order, external competition, revenue generation, economic growth, legitimation, and environmental conservation. As such, they present themselves as fundamental to the future of the Finnish state, its unique sociocultural characteristics, and its contested welfare society. The article concludes with a discussion on the harmful hopes that these industry lobbying campaigns provoke among both audiences and livelihood practitioners in the face of inevitable sustainability transitions.
Keywords: fur farming; peat extraction; industry lobbying; outside lobbying; core imperatives; sustainability transition